Mapping Research Trends and Thematic Evolution in Ethnomathematics 2020-2025: A Bibliometric Analysis in Mathematics Education - Fidella Justine Mulyadi; Rohati Rohati; Duano Sapta Nusantara (MASI Mandiri Edukasi, 2026)
This study maps the development of ethnomathematics research from 2020 to 2025 through a bibliometric analysis of Scopus-indexed publications. Using VOSviewer, publication trends, influential authors, institutional collaborations, and thematic structures were identified and visualised. The findings reveal substantial growth in ethnomathematics publications beginning in 2021, with Indonesia emerging as the most productive contributor. Four dominant thematic clusters were identified: teacher pedagogy, cultural artefacts and symbolism, cognitive development in geometry and spatial reasoning, and sociocultural knowledge systems. Visualisation analyses indicate a thematic transition from traditional cultural documentation toward innovation in instructional media and 21st-century learning approaches. The results highlight the pivotal role of teachers in mediating cultural knowledge within classroom practices. Overall, the study demonstrates that ethnomathematics is evolving into a multidimensional research field that integrates culture, education, cognition, and technology, while offering promising directions for future research in computational ethnomathematics, culturally responsive pedagogy, and digital learning environments.